2016
DOI: 10.1371/journal.pone.0157431
|View full text |Cite|
|
Sign up to set email alerts
|

The Gastroprotective Effect of Vitex pubescens Leaf Extract against Ethanol-Provoked Gastric Mucosal Damage in Sprague-Dawley Rats

Abstract: Vitex pubescens is a Malaysian therapeutic plant employed in traditional drug to remedy a variety of disorders. The purpose of this research is to assess the gastroprotective efficiency of V. pubescens leaves against ethanol-induced gastric hemorrhagic laceration in rats. Animals were randomly allocated into seven groups and pre-treated, separately, with 10% Tween 20 (normal and ulcer control groups), 20 mg/kg omeprazole (reference group), and 62.5, 125, 250, and 500 mg/kg of V. pubescens extract (experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…PGE2 can primarily protect gastric mucosal by stimulating gastric mucus and bicarbonate secretion, increasing the mucosal blood flow, suppressing the aggregation of leukocyte, and attenuating cytotoxic damage by participating in various mechanisms [5,39,44]. The present study demonstrated that compared with normal rats, the gastric mucosa PGE2 levels in the ethanol group rats were significantly reduced (Figure 2a), suggesting that ethanol causes the inactivation of prostaglandin synthase, which leads to a decrease in prostaglandin biosynthesis, which is in accordance with other related researches [4,5,8,30]. However, WOPs remarkably enhanced the level of PGE 2 in comparison with ethanol group, indicating that PGE2 participated in the defense mechanism of WOPs against ethanol-induced gastric mucosal injury.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…PGE2 can primarily protect gastric mucosal by stimulating gastric mucus and bicarbonate secretion, increasing the mucosal blood flow, suppressing the aggregation of leukocyte, and attenuating cytotoxic damage by participating in various mechanisms [5,39,44]. The present study demonstrated that compared with normal rats, the gastric mucosa PGE2 levels in the ethanol group rats were significantly reduced (Figure 2a), suggesting that ethanol causes the inactivation of prostaglandin synthase, which leads to a decrease in prostaglandin biosynthesis, which is in accordance with other related researches [4,5,8,30]. However, WOPs remarkably enhanced the level of PGE 2 in comparison with ethanol group, indicating that PGE2 participated in the defense mechanism of WOPs against ethanol-induced gastric mucosal injury.…”
Section: Discussionsupporting
confidence: 91%
“…However, the GUI of rats in the omeprazole group and whey protein group was lower than that of the ethanol group, but the difference was not significant (p > 0.05). The intervention dose of omeprazole positive control group was converted according to the recommended dosage to body weight ratio according to the drug instructions [4].…”
Section: Effect Of Wops On Gross Evaluation and Gastric Ulcer Index (mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Malaysian peninsula, Vitex pubescens Vahl. (Verbenaceae) is known as Halban [6]. Vitex or Vitex Pinnata was others scientific name for Halban trees.…”
Section: A Vitex Pubescens Vahl (Halban)mentioning
confidence: 99%
“…This tree has many advantages especially in medicine area [10][11][12]. A bark decoction is used to relieve stomach distress and a poultice of the leaves is used in fevers and injuries [13].…”
Section: A Vitex Pubescens Vahl (Halban)mentioning
confidence: 99%